Consistency in supplemental food availability affects the space use of wintering birds. (8th March 2021) - Mady, Rachael P; Hochachka, Wesley M; Bonter, David N
Abstract: Across the globe, millions of people feed wild birds and this practice has profound implications for many bird species. To better understand the effects of this supplemental feeding, many researchers have compared birds with access to inexhaustible supplemental food to those without access. However, the consistency of supplemental food availability varies with peoples' provisioning habits because some people fill their feeders daily, while others do so sporadically. As the consistency of food availability changes, a bird's foraging strategy, including its use of space, should change. To determine how space use varies with the consistency of supplemental food availability, we surveyed three species with access to experimental feeders that provided constant, pulsed, or no access to food. We conducted these surveys at two locations—near and far from the feeder—within nine sites to determine differences in space use among and within sites. Access to supplemental food, regardless of feeding regime, anchored the movements of each species near the feeders. However, the different feeding regimes had different effects on space use. Birds with constant access to supplemental food were continually anchored near the feeders, while the birds with pulsed access were temporarily anchored near the feeders. In one of three species (black-capped chickadee), birds concentrated in larger numbers near feeders with pulsed access when food was available compared to near feeders with constant access. Supplemental feeders act as spatial anchors but do so in different ways across species and feeding regimes with potentially varying implications for survival and population dynamics. Abstract : Millions of people feed birds, but the consistency of feeding varies, and so may the way in which birds travel through the space around feeding sites. We found that bird feeders attract and concentrate birds near them, but the strength of this attraction varies by species and depends on the consistency of food availability.